Bank capital, liquid reserves, and insolvency risk - Hugonnier, Julien; Morellec, Erwan (Journal of Financial Economics, 2017)
We develop a dynamic model of banking to assess the effects of liquidity and leverage requirements on banks’ financing decisions and insolvency risk. In this model, banks face taxation, issuance costs of securities, and default costs and maximize shareholder value by choosing their debt-to-asset ratio, deposits-to-debt ratio, liquid asset holdings, equity issuance and default policies in response to these frictions as well as regulatory requirements. Our analytic characterization of the bank policy choices shows that imposing liquidity requirements leads to lower bank losses in default at the cost of an increased likelihood of default. Combining liquidity and leverage requirements reduces both the likelihood of default and the magnitude of bank losses in default.